Combined Analysis of EPHX1, GSTP1, GSTM1 and GSTT1 Gene Polymorphisms in Relation to Chronic Obstructive Pulmonary Disease Risk and Lung Function Impairment. Issue 5 (28th May 2013) - Lakhdar, Ramzi; Denden, Sabri; Knani, Jalel; Leban, Nadia; Daimi, Houria; Hassine, Mohsen; Lefranc, Gérard; Chibani, Jemni Ben; Khelil, Amel Haj
Abstract : Smoking is considered as the major causal factor of chronic obstructive pulmonary disease (COPD). Nevertheless, a minority of chronic heavy cigarette smokers develops COPD. This suggests important contribution of other factors such as genetic predisposing. Our objective was to investigate combined role of EPHX1, GSTP1, M1 and T1 gene polymorphisms in COPD risk, its phenotypes and lung function impairment. Prevalence of EPHX1, GSTP1, M1 and T1 gene polymorphisms were assessed in 234 COPD patients and 182 healthy controls from Tunisia. Genotypes of EPHX1 (Tyr113His; His139Arg) and GSTP1 (Ile105Val; Ala114Val) polymorphisms were performed by PCR-RFLP, while the deletion in GSTM1 and GSTT1 genes was determined using multiplex PCR. Analysis of combinations showed a significant association of 113His/His EPHX1/null-GSTM1 (OR = 4.07) and null-GSTM1/105Val/Val GSTP1 (OR = 3.56) genotypes with increased risk of COPD (respectively P=0.0094 and P=0.0153). The null-GSTM1/ null-GSTT1, 105Val/Val GSTP1/null GSTT1, 113His/His EPHX1/null-GSTM1 and null-GSTM1/105Val/Val GSTP1 genotypes were related to emphysema (respectively P = 0.01; P = 0.009; P = 0.008 and P = 0.001). Combination of 113His/His EPHX1/null-GSTM1 genotypes showed a significant association with the decrease of ΔFEV1 in patients (P = 0.028). In conclusion, our results suggest combined EPHX1, GSTP1, GSTM1 and GSTT1 genetic polymorphisms may play a significant role in the development of COPD, emphysema and decline of the lung function.